Capture and transport of white rhinoceroses (Ceratotherium simum) cause shifts in their fecal microbiota composition towards dysbiosis - Pohlin F; Frei C; Meyer LCR; Roch F-F; Quijada NM; Conrady B; Neubauer V; Hofmeyr M; Cooper D; Stalder G; Wetzels SU (Oxford University Press and the Society for Experimental Biology, 2023)
Translocations of Rhinocerotidae are commonly performed for conservation purposes but expose the animals to a variety of stressors (e.g. prolonged fasting, confinement, novel environment, etc.). Stress may change the composition of gut microbiota, which can impact animal health and welfare. White rhinoceroses in particular can develop anorexia, diarrhea and enterocolitis after translocation. The aim of this study was to investigate the associations of age, sex and translocation on the rhinoceros' fecal bacterial microbiota composition. fecal samples were collected from rhinoceroses at capture (n = 16) and after a >30-hour road transport (n = 7). DNA was isolated from these samples and submitted for 16S rRNA V3-V4 phylotyping. Alpha diversity indices of the rhinoceros' fecal microbiota composition of different age, sex and before and after transport were compared using non-parametric statistical tests and beta diversity indices using Permutational Multivariate Analysis Of Variance (PERMANOVA). Resulting P-values were alpha-corrected (Padj.). Alpha and beta diversity did not differ between rhinoceroses of different age and sex. However, there was a significant difference in beta diversity between fecal samples collected from adult animals at capture and after transport. The most abundant bacterial phyla in samples collected at capture were Firmicutes and Bacteroidetes (85.76%), represented by Lachnospiraceae, Ruminococcaceae and Prevotellaceae families. The phyla Proteobacteria (Padj. = 0.009) and Actinobacteria (Padj. = 0.012), amongst others, increased in relative abundance from capture to after transport encompassing potentially pathogenic bacterial families such as Enterobacteriaceae (Padj. = 0.018) and Pseudomonadaceae (Padj. = 0.022). Important commensals such as Spirochaetes (Padj. = 0.009), Fibrobacteres (Padj. = 0.018) and Lachnospiraceae (Padj. = 0.021) decreased in relative abundance. These results indicate that the stressors associated with capture and transport cause an imbalanced fecal microbiota composition in white rhinoceroses that may lead to potentially infectious intestinal disorders. This imbalance may result from recrudescence of normally innocuous pathogens, increased shedding of pathogens or increased vulnerability to new pathogens.
Keywords: Age; diarrhea; hindgut; microbiome; sex; stress-response; translocation; wildlife